TANTANGAN DAN PELUANG: GADGET, KECERDASAN EMOSIONAL, DAN PEMBENTUKAN SIKAP SOSIAL PADA ANAK-ANAK SEKOLAH DASAR - Rosalia Eka Lusiana; Dini Rahmawati; Arri Handayani (STKIP Subang, 2024)
The development of existing technology and information makes everyone never escape from the grasp of gadgets. The use of gadgets has permeated various walks of life, including elementary school children. The benefits of using gadgets in elementary school children due to the ease of accessing information, entertainment, games, interactive learning and as a reinforcement of technological skills are part of the children's experience in the digital era. The use of gadgets from year to year is increasing, causing changes in user behavior, including children. This behavior change is a deep concern because it affects the growth of emotional intelligence, empathy, and interpersonal relationships of children towards the formation of social attitudes in elementary school. This imbalance raises challenges as well as positive opportunities as a learning approach that supports the development of emotional intelligence and social attitudes for elementary school children in the digital age. A deep understanding of challenges and opportunities is expected to guide a balanced pedagogical and policy approach in harnessing the positive potential of gadgets to support the holistic growth of primary school children in the digital age.